Artificial Intelligence in English Teaching at an Islamic University Language Center - Alka Fajari; Dody Truna; Aep Kusnawan; Siti Fatimah (Wanastra: Jurnal Bahasa dan Sastra, 2026)
This study aims to describe the use of Artificial Intelligence (AI) in English language teaching at the Language Center of UIN Sunan Gunung Djati Bandung. The development of AI has brought changes in language learning practices, particularly in the preparation of materials, providing feedback, and developing students' writing skills. However, its implementation also raises challenges related to academic integrity and the potential for student dependence on technology. This study uses a qualitative descriptive approach involving three Language Center instructors as participants. Data were obtained through interviews, observations, and data analysis. The results show that AI helps the language learning process at the Language Center of UIN Sunan Gunung Djati Bandung and that AI does not overhaul teaching pedagogy, but rather strengthens existing pedagogical orientations. Although it provides the benefits of efficiency and flexibility, the use of AI still requires ethical guidelines and pedagogical oversight. This study concludes that AI has the potential to improve the quality of English language teaching if it is integrated responsibly in the context of higher education